Combined effects of agrochemicals and ecosystem services on crop yield across Europe. (12th September 2017) - Gagic, Vesna; Kleijn, David; Báldi, András; Boros, Gergely; Jørgensen, Helene Bracht; Elek, Zoltán; Garratt, Michael P. D.; de Groot, G. Arjen; Hedlund, Katarina; Kovács‐Hostyánszki, Anikó; Marini, Lorenzo; Martin, Emily; et al.
Abstract: Simultaneously enhancing ecosystem services provided by biodiversity below and above ground is recommended to reduce dependence on chemical pesticides and mineral fertilisers in agriculture. However, consequences for crop yield have been poorly evaluated. Above ground, increased landscape complexity is assumed to enhance biological pest control, whereas below ground, soil organic carbon is a proxy for several yield‐supporting services. In a field experiment replicated in 114 fields across Europe, we found that fertilisation had the strongest positive effect on yield, but hindered simultaneous harnessing of below‐ and above‐ground ecosystem services. We furthermore show that enhancing natural enemies and pest control through increasing landscape complexity can prove disappointing in fields with low soil services or in intensively cropped regions. Thus, understanding ecological interdependences between land use, ecosystem services and yield is necessary to promote more environmentally friendly farming by identifying situations where ecosystem services are maximised and agrochemical inputs can be reduced.